Avaliação da reação em cadeia da polimerase (PCR) em amostras de fezes para diagnóstico da esquistossomose em região de baixa endemicidade no Estado do Ceará - Carneiro, Teiliane Rodrigues (2011)
Schistosomiasis is still a public health problem in Brazil. The infection is widespread in southeast and northeast. The laboratorial diagnosis of schistosome infection has been based on direct coproscopic examination and by indirect methods for detection of antigen, antibodies and specific DNA fragments that are associated with Schistosoma mansoni infection. The aim of the present study was to evaluate polymerase chain reaction (PCR) designed for detection of Schistosoma mansoni DNA in individuals from a low endemic area in Ceará state. The study was conducted in the Planalto do Cajueiro, Maranguape, Ceará, Brazil. In the laboratory performed the ELISA for detection of IgG antibodies against adult worms antigen of S. mansoni, and stool examinations (Kato-Katz, Lutz, Saline gradient and Helmintex® methods), considering the results obtained, for distribution of 56 stool samples selected among the 125 examined, in the following groups: Group I - ELISA reactive / Others parasites (+ ), Group II- ELISA reactive / Others parasites (-), Group III- ELISA non reactive / Others parasites (+), Group IV- ELISA non reactive / Others parasites (-), Group V- ELISA reactive / Coproscopic examination S. mansoni (+).The PCR was carried out according to a protocol described by Pontes et al.(2002) . Group I, 02 of 10 samples were positive in PCR; Group II, 04 of 10 samples were positive by PCR and in Group III, 01 of 07 samples were positive in PCR. Among the 10 samples of Group IV, 01 was positive in PCR and Group V, 13 of 19 samples were positive in PCR. Among the 39 individuals who showed reactivity by ELISA, 06 samples were positive in coproscopic examination and PCR was reactive in 19 samples. Comparing the results in Group V, with the Kato-Katz, this method detected 06 individuals, while PCR detected 13 individuals were positive. By comparing the PCR of Saline gradient, it is observed that the Saline gradient detected 09 individuals, while PCR detected 11. When comparing PCR to Helmintex®, we found that the Helmintex® detected 10, while PCR detected 08 samples. We conclude that PCR is an important tool to improve the sensitivity in detecting S. mansoni infection in low endemic areas. We emphasize that is very important associate the exams in order to achieve the real diagnosis of the disease.